Proceedings of the 19th ACM SIGSOFT Symposium and the 13th European Conference on Foundations of Software Engineering 2011
DOI: 10.1145/2025113.2025129
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication of software development knowledge through community portals

Abstract: Knowledge management plays an important role in many software organizations. Knowledge can be captured and distributed using a variety of media, including traditional help files and manuals, videos, technical articles, wikis, and blogs. In recent years, web-based community portals have emerged as an important mechanism for combining various communication channels. However, there is little advice on how they can be effectively deployed in a software project.In this paper, we present a first study of a community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This participation provides higher levels of social transparency [34] about the identity of internal developers therefore allowing external developers to interact with them. To illustrate this point, our data shows that Android developers (who work for Google) use specific communication channels to disseminate information about the documentation and official releases [35], so by taking advantage of their level of social transparency in social media they can promote the Android ecosystem to "external" developers.…”
Section: " [A14]mentioning
confidence: 98%
“…This participation provides higher levels of social transparency [34] about the identity of internal developers therefore allowing external developers to interact with them. To illustrate this point, our data shows that Android developers (who work for Google) use specific communication channels to disseminate information about the documentation and official releases [35], so by taking advantage of their level of social transparency in social media they can promote the Android ecosystem to "external" developers.…”
Section: " [A14]mentioning
confidence: 98%
“…Treude et al evaluated the nature of questions asked on StackOverflow with respect to programming language, question tags, and question types determined by manual coding of a sample of questions. They concluded that the community answers review, conceptual, and how-to questions more frequently than any other type, with review questions achieving a 92% accepted answer rate [21]. Posnett et al studied the nature of expertise among Stack Exchange participants and found that participation in online Q/A sites does not necessarily lead to increased expertise as measured by peer scoring [16].…”
Section: Related Workmentioning
confidence: 99%
“…T HE knowledge needed by software developers is captured in many forms of documentation, typically written by different individuals [53]. Despite the best efforts of documentation writers [14], there often remains a mismatch between the needs of documentation consumers and the knowledge provided in developer documentation.…”
Section: Introductionmentioning
confidence: 99%